Understanding Cybercrime in Developing Economies: Insights from Agona Swedru, Ghana - Charles Obeng; Paul Kwasi Kumah; Hubert Bimpeh Asiedu; Felix Awuah Obeng Senior (E-Journal of Humanities, Arts and Social Sciences)
The purpose of this study was to explore the prevalence and primary causes of cybercrime in Agona Swedru. Using a quantitative research survey and a simple random sampling technique, 397 individuals were surveyed. The study’s data were analyzed using both frequencies, cross tabulation and linear regression. The findings highlight that a significant proportion of the population engages in cybercrime, with online romance scams and financial fraud being the common forms of cybercrime being practiced. Unemployment, financial constraints, and poverty were identified as primary causes, pushing individuals towards cybercrime as a means to achieve financial stability. Based on the findings, it is recommended that enhancing employment opportunities through vocational training and job creation programs can alleviate the strain caused by unemployment. Also, establishing financial aid programs and counseling services can help individuals manage financial pressures. Implementing these recommendations will create a more stable and supportive environment, reducing the factors that drive individuals toward cybercrime. By identifying socioeconomic factors, such as unemployment and poverty, as key drivers of cybercrime, this study enhances understanding of the motivations behind cybercrime in Agona Swedru and similar contexts.